2012
DOI: 10.1038/modpathol.2011.176
|View full text |Cite
|
Sign up to set email alerts
|

ERG immunohistochemistry is not predictive for PSA recurrence, local recurrence or overall survival after radical prostatectomy for prostate cancer

Abstract: In prostate cancer genomic rearrangements involving genes encoding ETS transcription factors are commonly present, with androgen-regulated transmembrane protease, serine 2 (TMPRSS2)-v-ets erythroblastosis virus E26 oncogen homologue (ERG) gene fusion occurring in 40-70%. Studies on the predictive value of ERG rearrangement as detected by in-situ hybridization or polymerase chain reaction have resulted in varying outcomes. The objective of this study was to correlate immunohistochemical ERG protein expression w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
86
7
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(118 citation statements)
references
References 36 publications
(59 reference statements)
22
86
7
3
Order By: Relevance
“…11,32 ERG immunoreactivity was present in half of the primary prostate cancers being consistent with the frequency of TMPRSS2-ERG fusion and the findings of other immunohistochemical studies. 11,33,34 We found an expression of ERG in approximately half of the lymph node metastases similar to the study of Hoogland et al 33 with six out of nine lymph nodes expressing ERG. In distant metastases, fluorescence in situ hybridization analyses have shown an occurrence of TMPRSS2-ERG rearrangements in 25-35%.…”
Section: Discussionsupporting
confidence: 89%
“…11,32 ERG immunoreactivity was present in half of the primary prostate cancers being consistent with the frequency of TMPRSS2-ERG fusion and the findings of other immunohistochemical studies. 11,33,34 We found an expression of ERG in approximately half of the lymph node metastases similar to the study of Hoogland et al 33 with six out of nine lymph nodes expressing ERG. In distant metastases, fluorescence in situ hybridization analyses have shown an occurrence of TMPRSS2-ERG rearrangements in 25-35%.…”
Section: Discussionsupporting
confidence: 89%
“…Ten studies reported the prognostic value of the gene fusion in radical prostatectomy (RP) cohorts [19][20][21][22][23][24][25][26][27][28]. In 6 of the 10 studies, TMPRSS2:ERG fusion status was not associated with outcome after surgery [19,21,22,24,27,29].…”
Section: Tmprss2:erg Fusionmentioning
confidence: 99%
“…Ten studies reported the prognostic value of the gene fusion in radical prostatectomy (RP) cohorts [19][20][21][22][23][24][25][26][27][28]. In 6 of the 10 studies, TMPRSS2:ERG fusion status was not associated with outcome after surgery [19,21,22,24,27,29]. In one Urine-detected rearrangement associated with positive repeat biopsy aCGH = array comparative genomic hybridization; ADT = androgen-deprivation therapy; AS = active surveillance; BCR = biochemical recurrence; CRPC = castration-resistant prostate cancer; DSS = disease-specific survival; FISH = fluorescence in situ hybridization; HR = hazard ratio; IHC = immunohistochemistry; IMRT = intensity-modulated radiation therapy; NA = not applicable; NR = not reported; OS = overall survival; PCa = prostate cancer; PSA = prostate-specific antigen; RT-PCR = reverse transcriptase polymerase chain reaction; RP = radical prostatectomy; SNP = single nucleotide polymorphism; TURP = transurethral resection of prostate; WW = watchful waiting.…”
Section: Tmprss2:erg Fusionmentioning
confidence: 99%
“…Recent work, however, failed to confirm that TMPRSS2:ERG correlates with adverse tumor characteristics and unfavorable prognosis (10,11). Nonetheless, this fusion is a likely initiating event in prostate cancer development representing a separate etiology with unique expression and epigenetic profiles (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%